COERCION INTO ADDICTION TREATMENT AND SUBSEQUENT SUBSTANCE USE PATTERNS AMONG PEOPLE WHO USE ILLICIT DRUGS IN VANCOUVER, CANADA - Pilarinos, Andreas (Addiction, 2019)
BACKGROUND AND AIMS: Many people who use drugs (PWUD) are coerced into receiving treatment. This study aimed to assess changes in substance use and related outcomes before versus after treatment in people coerced into treatment, voluntarily attending treatment or not attending treatment. DESIGN: Data from three linked prospective cohort studies of PWUD were used. McNemar’s test and non-linear growth curve modeling were employed to: a) assess changes in substance use patterns before and after coerced addiction treatment and b) compare these changes with changes in PWUD who 1) voluntarily accessed and 2) did not access treatment. SETTING: Vancouver, Canada. PARTICIPANTS: 3,196 community-recruited PWUD. MEASUREMENTS: The outcome variables were substance use and related outcomes assessed by self-reported questionnaire. The input variable was self-reported coerced addiction treatment (defined as being forced into addiction treatment by a doctor or the criminal justice system), voluntary treatment versus no treatment. FINDINGS: Between September 2005 and June 2015, 399 (12.5%) participants reported being coerced into addiction treatment. In McNemar’s test, there were no statistically significant reductions in within-group substance use outcomes for people coerced into treatment, voluntarily attending treatment or not attending treatment. In non-linear growth curve analyses, there were no statistically significant differences in the before and after substance use patterns between those coerced into treatment versus either of the two control groups (all p>0.05). In sub-analyses, we found no statistically significant differences in substance use patterns between people who reported formal coerced treatment through the criminal justice system and people who reported informal coerced treatment through a physician. CONCLUSIONS: Among PWUD in Vancouver, Canada, there appear to be no statistically significant improvements in substance use outcomes among those reporting coerced addiction treatment, those voluntarily accessing treatment, and those not attending treatment.